2021
DOI: 10.3390/brainsci12010016
|View full text |Cite
|
Sign up to set email alerts
|

Regional Topological Aberrances of White Matter- and Gray Matter-Based Functional Networks for Attention Processing May Foster Traumatic Brain Injury-Related Attention Deficits in Adults

Abstract: Traumatic brain injury (TBI) is highly prevalent in adults. TBI-related functional brain alterations have been linked with common post-TBI neurobehavioral sequelae, with unknown neural substrates. This study examined the systems-level functional brain alterations in white matter (WM) and gray matter (GM) for visual sustained-attention processing, and their interactions and contributions to post-TBI attention deficits. Task-based functional MRI data were collected from 42 adults with TBI and 43 group-matched no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 109 publications
2
1
0
Order By: Relevance
“…Our findings suggest that this disruption to the brain functional network following mTBI might contribute to the deficits in visuospatial/executive performance and complex cognitive processes present after mTBI. Furthermore, for nodal properties, significantly altered nodal efficiencies in several nodes were reported in the mTBI group, mainly including the precuneus, post cingulate gyrus, and temporal lobe, partly consistent with a previous study (32). Meanwhile, this study showed disrupted node degree centrality in some regions, such as the frontal, temporal, and parietal lobes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings suggest that this disruption to the brain functional network following mTBI might contribute to the deficits in visuospatial/executive performance and complex cognitive processes present after mTBI. Furthermore, for nodal properties, significantly altered nodal efficiencies in several nodes were reported in the mTBI group, mainly including the precuneus, post cingulate gyrus, and temporal lobe, partly consistent with a previous study (32). Meanwhile, this study showed disrupted node degree centrality in some regions, such as the frontal, temporal, and parietal lobes.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, for nodal properties, significantly altered nodal efficiencies in several nodes were reported in the mTBI group, mainly including the precuneus, post cingulate gyrus, and temporal lobe, partly consistent with a previous study (32). Meanwhile, this study showed disrupted node degree centrality in some regions, such as the frontal, temporal, and parietal lobes.…”
Section: Discussionsupporting
confidence: 91%
“…Their findings provide evidence concerning the temporal instability of the functional connectivity associated with TBI-related attention deficits in children. In the fourth article, the same research group [4] also examined alterations in the functional network organization and connectivity in both white matter (WM) and gray matter (GM) during sustained attention processing in adults with post-TBI attention deficits. The authors found significant alterations in functional integration and segregation in several WM and GM regions involved in visually sustained attention processing in the TBI group compared to healthy controls.…”
mentioning
confidence: 99%